Cécile Chaminade: imaginative genius, ephemeral star - Worster, Skye Kathleen (My University, 2020)
This dissertation has emerged out of my deep fascination for French female composer and pianist, Cécile Chaminade, as well as my growing recognition of the need for forgotten women in music to be unearthed and given the credit they so deserve. While there have been many great female musicians and composers such as Clara Schumann, Amy Beach or Ethel Smyth who warrant recognition in their own right, Chaminade is unique in the impact she made on the audiences of her day, in her output of music that was so adored and the celebrity status she achieved in a way that no other female composer has attained. Chaminade enjoyed unprecedented success in the period 1890 to 1910 yet, despite her fame, she died in relative obscurity in 1944; it seemed as if her legacy was to be consigned to the same abyss shared by so many female musicians. Feminist musicology, though, has seen major strides in recent years and, since the publication of Marcia Citron’s book, Cécile Chaminade: A Bio-Bibliography in 1988, research on Chaminade has been on the rise. Citron, by virtue of being the major authority on Chaminade and her work, has served as the most important source for my purposes. This dissertation builds on extant information about Chaminade and presents a detailed overview of her musical upbringing, education and career as both pianist and composer, provides context on some of her French contemporaries, and explores her musical style across her career, identifying stylistic patterns and trademarks in her work. This project has extended far beyond merely researching and writing about Chaminade for my Master’s degree and has involved tracing her footsteps in Paris, which led me to her home and her grave; uncovering her family tree and history; listening to, playing and analysing her music; scrutinising critical reviews; performing a selection of her works in an all-female recital; and presenting her as Composer of the Week on Classic 1027’s “Full Works” in commemoration of the 75th anniversary of her death in 2019. The last entailed selecting and sourcing five works to be broadcast and writing a script for the introduction of each work which I presented on air. The works included Chaminade’s Concertstück, Sonata, op. 21, Callirhoë, Piano Trio No. 2 and five songs: La lune paresseuse, Nice-la-belle, Espoir, L’été and Chanson triste
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Music in the Wits School of Arts, Faculty of Humanities, University of the Witwatersrand, 2020